A path- analytic model of schooling situations and secondary school students' academic performance in Oyo state, Nigeria. (2002)
This study investigated the extent to which schooling situations variables ( resource situation, average class size,or population, or quantity and quality of teachers and number of furnished classrooms) predict secondary schoolacademic performances in Oyo state of Nigeria in 2000/2001 school session. It was conducted ex-post facto under a non experimental survery research design. 100 out of the secondary schools in Oyo State were randomly selected for the study. The study adopted the use of a confirmatory causal modeling method of analysis. This involves two closely related analytical techniques: multiple regression and path analysis. Findings of the study revealed that out of the six variables htypothesized to influence students' academic performance, four of them ( student- teacher ratio, teacher population, resource situation and students' population) have both direct and indirect effect on students' academic performance while the remaining two variables (number of classroom and average class size) have indirect effects on students academic performance. In all 50.92% of the total effect of all the six independent variables on students' academic performance are direct and indirect while 25.08% are indirect. The implications of the findings are discussed.